2017
DOI: 10.4049/jimmunol.1701134
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: c-Maf Is Required for Regulatory T Cells To Adopt RORγt+ and Follicular Phenotypes

Abstract: Regulatory T cells (Tregs) adopt specialized phenotypes defined by co-expression of lineage-defining transcription factors (TFs) – such as RORγt, Bcl-6, or PPARγ – alongside FoxP3. These Treg subsets have unique tissue distributions and diverse roles in maintaining organismal homeostasis. However, despite extensive functional characterization, the factors driving Treg specialization are largely unknown. Here, we show that c-Maf is a critical TF regulating this process in mice, essential for generation of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 30 publications
7
52
1
Order By: Relevance
“…While the majority of colonic Tregs express Gata3 , the number of Rorc -expressing cells is low, and they do not appear to form a distinct subpopulation (Supplementary Figure 4A). Interestingly, the recently identified Rorc -regulator Maf (Wheaton, Yeh, and Ciofani 2017) is frequently expressed in both colon and skin Tregs, despite not contributing to the definition of colonic Treg subpopulations (Supplementary Figure 4B).…”
Section: Cd4 + Treg Are Transcriptionally Distinct Across Tissuesmentioning
confidence: 99%
“…While the majority of colonic Tregs express Gata3 , the number of Rorc -expressing cells is low, and they do not appear to form a distinct subpopulation (Supplementary Figure 4A). Interestingly, the recently identified Rorc -regulator Maf (Wheaton, Yeh, and Ciofani 2017) is frequently expressed in both colon and skin Tregs, despite not contributing to the definition of colonic Treg subpopulations (Supplementary Figure 4B).…”
Section: Cd4 + Treg Are Transcriptionally Distinct Across Tissuesmentioning
confidence: 99%
“…2E). On the other hand, C3 Tregs express genes required for follicular regulatory phenotype (C3: Maf (37)) and genes that promote Treg survival and persistence (C3: Nr4a2, Cst7) ( Fig. 2E and 3C, Fig.…”
Section: Molecular Characterization Of Resting Primed and Activatedmentioning
confidence: 99%
“…The spleen uniquely contains a high frequency of activated Tregs (C3-20 activated Tregs) expressing Nr4a2, a Foxp3-binding transcription factor (70), Cst7(71), a marker for previous Treg activation and regulator of cytotoxicity, and Izumo1r(45), a marker for natural Tregs in the spleen. Compared with other activated Treg cluster C4, C3-activated cluster also differentially express Tbc1d4 and Maf, transcription factors for follicular regulatory T cells(37,72). Given the role of the spleen in immune surveillance and its lymphatic connection to peripheral tissues as well as germinal center formation(73), these splenic Nr4a2 + Tregs may include follicular regulatory T cells (Tfr) and recently activated Tregs licensed to exit the spleen and migrate into sites of inflammation.…”
mentioning
confidence: 99%
“…However, these observations can be largely explained by a general requirement for BATF in the initial differentiation of eTregs, such that BATF expression is important for all tissue Tregs but does not convey tissue specificity of gene expression 11 . Conversely, we and others recently showed that the bZIP TF c-Maf is essential for the differentiation of both follicular regulatory T (Tfr) cells and ROR γ t + Tregs, but does not play a role in differentiation of either eTregs or VAT Tregs, demonstrating that bZIP TFs can play tissue or subset-restricted roles in Treg biology 12, 13 . Nevertheless, outside of these limited examples, the function of the vast majority of bZIP/AP-1 TFs in Treg biology remains unexplored.…”
Section: Introductionmentioning
confidence: 93%